2014
DOI: 10.1002/ange.201410186
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative Radical Coupling of α‐Aminoacyl Tellurides: Single‐Step Preparation of γ‐Amino and α,β‐Diamino Acids and Rapid Synthesis of Gabapentin and Manzacidin A

Abstract: A new radical-based coupling method has been developed for the single-step generation of various g-amino acids and a,b-diamino acids from a-aminoacyl tellurides. Upon activation by Et 3 B and O 2 at ambient temperature, a-aminoacyl tellurides were readily converted into a-amino carbon radicals through facile decarbonylation, which then reacted intermolecularly with acrylates or glyoxylic oxime ethers. This mild and powerful method was effectively incorporated into expeditious synthetic routes to the pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Asymmetric synthesis of an α-AA derivative 63 by conjugate addition of radical to a chiral glyoxylic oxime ether 57 (Inoue, 2015). [149] Scheme 32. Asymmetric synthesis of the β-AA derivatives 65 by conjugate addition of carbon radicals to a chiral glyoxylic oxime ether 64 and the isolation of α,β-substituted β-AA derivative 66 .…”
Section: Chiral 25-diketopiperazine Derivatives As Substratesmentioning
confidence: 99%
See 4 more Smart Citations
“…Asymmetric synthesis of an α-AA derivative 63 by conjugate addition of radical to a chiral glyoxylic oxime ether 57 (Inoue, 2015). [149] Scheme 32. Asymmetric synthesis of the β-AA derivatives 65 by conjugate addition of carbon radicals to a chiral glyoxylic oxime ether 64 and the isolation of α,β-substituted β-AA derivative 66 .…”
Section: Chiral 25-diketopiperazine Derivatives As Substratesmentioning
confidence: 99%
“…[148] In 2015 Nagatomo et al found a practical application of the radical approach for the asymmetric synthesis of an α,β-diamino acid derivative 63 (Scheme 31). [149] The triethyl borane/O 2 mediated [137] decarbonylative radical coupling of α-aminoacyl telluride with an Oppolzer's camphor sultam derivative of glyoxylic oxime ether 57 at ambient temperature afforded the desired α,β-diamino acid derivative 63 in a 94% yield, albeit the dr was low (3.3:1) (Scheme 31). It was assumed that an α-aminoacyl telluride was readily converted into α-amino carbon radical through facile decarbonylation, which then reacted intermolecularly with a glyoxylic oxime ether 57 (Scheme 31).…”
Section: Chiral Oxime Derivatives As Substratesmentioning
confidence: 99%
See 3 more Smart Citations